2006
DOI: 10.1021/es060679s
|View full text |Cite
|
Sign up to set email alerts
|

Regional Public Health Cost Estimates of Contaminated Coastal Waters:  A Case Study of Gastroenteritis at Southern California Beaches

Abstract: We present estimates of annual public health impacts, both illnesses and cost of illness, attributable to excess gastrointestinal illnesses caused by swimming in contaminated coastal waters at beaches in southern California. Beachspecific enterococci densities are used as inputs to two epidemiological dose-response models to predict the risk of gastrointestinal illness at 28 beaches spanning 160 km of coastline in Los Angeles and Orange Counties. We use attendance data along with the health cost of gastrointes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
46
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 31 publications
(54 reference statements)
0
46
0
Order By: Relevance
“…The related degradation of the water quality increases human health risks and leads to large economic impacts Given et al, 2006]. Terrestrial storm water runoff often drains first onto rivers and tidal channels, finding its way into the coastal zone with freshwater inflows.…”
Section: Introductionmentioning
confidence: 99%
“…The related degradation of the water quality increases human health risks and leads to large economic impacts Given et al, 2006]. Terrestrial storm water runoff often drains first onto rivers and tidal channels, finding its way into the coastal zone with freshwater inflows.…”
Section: Introductionmentioning
confidence: 99%
“…Coastal tourism is the largest market segment of global tourism [2][3][4]. At California beaches, each year nearly 150-400 million visits generated billions of dollars expenditures [5]. On the Miami Beach, more than 2 million visitors per annum brought over $130 million federal tax revenue [6].…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have reported usage frequency for swimmers and non-swimmers based on records of lifeguards stands, 3,4 or conducted randomized trials for evaluating exposure differences between bathers and non-bathers. 5 At least one study used aerial photographs in conjunction with interviews of state officials.…”
Section: Introductionmentioning
confidence: 99%